2021
DOI: 10.1111/jasp.12814
|View full text |Cite
|
Sign up to set email alerts
|

Social class and wellbeing among staff and students in higher education settings: Mapping the problem and exploring underlying mechanisms

Abstract: For both staff and students within UK Higher Education (HE), wellbeing -an index of both physical and mental health -is notoriously poor. Amongst UK-based University staff, around half (49%) experience high levels of psychological distress and are at risk of psychological illness. This exceeds the proportion found within other professional groups in the population generally (around 22%), and is comparable with those recently made unemployed (52%; see Kinman et al., 2006). Numerous studies converge in concludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
(158 reference statements)
1
2
0
Order By: Relevance
“…Whilst the relationship between SES and perceived worth was significant, the association between perceived worth and mental health and wellbeing was non-significant in our model. This extends and qualifies previous research that has suggested the fulfilment of perceived worth as an explanation for socioeconomic disparities in mental health and wellbeing among university students [ 21 , 24 ]. Given that the addition of competence is the key feature differentiating the present research from previous work, we suggest that, in the present sample, competence accounts for some of the association between perceived worth and mental health and wellbeing.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Whilst the relationship between SES and perceived worth was significant, the association between perceived worth and mental health and wellbeing was non-significant in our model. This extends and qualifies previous research that has suggested the fulfilment of perceived worth as an explanation for socioeconomic disparities in mental health and wellbeing among university students [ 21 , 24 ]. Given that the addition of competence is the key feature differentiating the present research from previous work, we suggest that, in the present sample, competence accounts for some of the association between perceived worth and mental health and wellbeing.…”
Section: Discussionsupporting
confidence: 88%
“…In a large cross-sectional sample of university students, we found evidence of socioeconomic inequalities in mental health and wellbeing, whereby subjective SES was associated with positive ( r = .30, p < .001) and negative ( r = -.16, p < .001) mental health and wellbeing. Socioeconomic inequalities in mental health and wellbeing are well established among the general population [ 14 ], and previous research suggests socioeconomic disparities are also found within university student populations [ 8 , 24 ]. The present research replicates these findings and extends previous work as it distinguishes between positive ( e .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation